The Impact of Caesarean Section and Place of Delivery on Utilization of Postpartum Care in Bangladesh - Tonasih Tonasih; Vianty Mutya Sari; Wiwin Widayanti; Md. Nadim Reza (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
Postpartum care is a critical component of maternal health, as it helps prevent complications and ensures the well-being of both mother and newborn. Despite global improvements in maternal healthcare, disparities in postpartum care utilization remain a significant public health concern, particularly in low- and middle-income countries such as Bangladesh. This study aimed to examine the impact of caesarean section and place of delivery on the utilization of postpartum care among women in Bangladesh. A cross-sectional study was conducted using nationally representative survey data, analyzing women who had delivered at health facilities. Univariate analysis described the distribution of sociodemographic characteristics and delivery-related factors, while bivariate analysis employed Chi-square tests to examine associations between independent variables and postpartum care utilization. Multivariate analysis using binary logistic regression assessed the adjusted impact of caesarean section, place of delivery, prenatal care, and household wealth on postpartum care uptake. The results revealed that women who delivered by non-caesarean section were 55% less likely to utilize postpartum care compared to those delivered via caesarean section. Women who delivered at private health facilities were 1.22 times more likely to utilize postpartum care than those at public facilities. Not receiving prenatal care decreased the probability of postpartum care by 55%, while women from the fourth wealth quintile and richest households were 1.58 and 2.60 times more likely, respectively, to access postpartum services compared to the poorest households. These findings underscore the importance of promoting equitable access to postpartum care, particularly for women delivering vaginally, at public facilities, or from lower-income households. Targeted policies that train providers in standardized postpartum care, strengthen follow-up through digital reminders and community health workers, and expand access in underserved areas can reduce disparities and improve maternal health outcomes in Bangladesh.